New unified H∞ dynamic observer design for linear systems with unknown inputs. (March 2016) - Gao, Nan; Darouach, Mohamed; Voos, Holger; Alma, Marouane
Abstract: In this paper, a unified H ∞ dynamic observer (UO) is proposed for a class of linear systems in the presence of unknown inputs and disturbances. It generalizes the existing results on the proportional observer (PO), the proportional integral observer (PIO) and the dynamic observer (DO). The design approach of the UO is derived from the solution of the linear matrix inequality (LMI), based on the new dynamic observer formulation and the solution of the algebraic constraints obtained from the unbiased estimation error. A numerical example is provided to show the applicability and the performance of our results.